2009
DOI: 10.1007/s10346-009-0157-4
|View full text |Cite
|
Sign up to set email alerts
|

Relations between hydrology and velocity of a continuously moving landslide—evidence of pore-pressure feedback regulating landslide motion?

Abstract: We measured displacement, pore-water pressure, and climatic conditions for 3 years at the continuously moving Slumgullion landslide in Colorado, USA. The landslide accelerated when pore-water pressure increased within the landslide body, but this occurred as pore-water pressure decreased along the landslide margin. The decrease probably occurred in response to shearinduced soil dilation at rates greater than pore-pressure diffusion and likely increased resistance to shear displacement and resulted in landslide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
138
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(146 citation statements)
references
References 29 publications
7
138
0
1
Order By: Relevance
“…Such models are able to describe both slow sliding and catastrophic failure because dilatant strengthening occurs only until a critical-state porosity is reached; subsequent consolidation can trigger catastrophic failure. Hence, although dilatant effects can be significant in particular cases (10), their ability to regulate the speeds of repeated slow-moving landslides is diminished if the shear-zone material cannot consolidate gradually between slip events.…”
mentioning
confidence: 99%
“…Such models are able to describe both slow sliding and catastrophic failure because dilatant strengthening occurs only until a critical-state porosity is reached; subsequent consolidation can trigger catastrophic failure. Hence, although dilatant effects can be significant in particular cases (10), their ability to regulate the speeds of repeated slow-moving landslides is diminished if the shear-zone material cannot consolidate gradually between slip events.…”
mentioning
confidence: 99%
“…The variation of mechanical state, such as the transformation from a relatively stable state to a critical state, has been commonly used to analyze the initiation of landslides (Iverson et al, 2010(Iverson et al, , 2000Liang et al, 2017;Sassa, 1984;Schulz et al, 2009). Therefore, a deep understanding of the soil state is the scientific basis for the study of landslide occurrence (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s, critical state soil mechanics has received extensive attention (Fleming et al, 1989;Gabet and Mudd, 2006;Iverson et al, 2000). Some of the observed landslides, such as the Salmon Creek landslide in Marin County (Fleming et al, 1989), Slumgullion landslide in Colorado (Schulz et al, 2009), and Guangming New Distinct landslide in Shenzhen (Liang et al, 2017), could be approximately explained by this theory. Based on the F line drawn by Casagrande (1936), Fleming et al (1989) found that the increase in pore water pressure contributed to the dilation and caused the debris flow characterized by the intermittent movement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reid and Iverson, 1992;Iverson, 2000;Wilkinson et al, 2002;Lindenmaier et al, 2005;Schulz et al, 2009;Wienhöfer et al, 2010;Bogaard et al, 2012). As a result, the effects of changes in climate or land use on landslide occurrence are difficult to predict (e.g.…”
Section: Introductionmentioning
confidence: 99%